Crassaminicella thermophila sp. nov., a moderately thermophilic bacterium isolated from a deep-sea hydrothermal vent chimney and emended description of the genus Crassaminicella. Issue 11 (26th November 2021) - Li, Xue-Gong; Lin, Jin; Bai, Shi-Jie; Dai, Jie; Jiao, Ze-Xi; Tang, Hong-Zhi; Qi, Xiao-Qing; Zhang, Wei-Jia; Liu, Min; Xu, Jian-Sheng; Wu, Long-Fei
Abstract : A novel moderately thermophilic, anaerobic, heterotrophic bacterium (strain SY095 T ) was isolated from a hydrothermal vent chimney located on the Southwest Indian Ridge at a depth of 2730 m. Cells were Gram-stain-positive, motile, straight to slightly curved rods forming terminal endospores. SY095 T was grown at 45–60 °C (optimum 50–55 °C), pH 6.0–7.5 (optimum 7.0), and in a salinity of 1–4.5 % (w/v) NaCl (optimum 2.5 %). Substrates utilized by SY095 T included fructose, glucose, maltose, N -acetyl glucosamine and tryptone. Casamino acid and amino acids (glutamate, glutamine, lysine, methionine, serine and histidine) were also utilized. The main end products from glucose fermentation were acetate, H2 and CO2 . Elemental sulphur, sulphate, thiosulphate, sulphite, fumarate, nitrate, nitrite and Fe(III) were not used as terminal electron acceptors. The predominant cellular fatty acids were C14 : 0 (60.5%) and C16 : 0 (7.6 %). The main polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, five unidentified phospholipids and two unidentified aminophospholipids. No respiratory quinones were detected. The chromosomal DNA G+C content was 30.8 mol%. The results of phylogenetic analysis of the 16S rRNA gene sequences indicated that SY095 T was closely related to Crassaminicella profunda Ra1766H T (95.8 % 16S rRNA gene sequence identity). SY095 T exhibited 78.1 % average nucleotide identity (ANI) to C. profunda Ra1766H T . The in silico DNA–DNA hybridization (DDH) value indicated that SY095 T shared 22.7 % DNA relatedness with C. profunda Ra1766H T . On the basis of its phenotypic, genotypic and phylogenetic characteristics, SY095 T is suggested to represent a novel species of the genus Crassaminicella, for which the name Crassaminicella thermophila sp. nov. is proposed. The type strain is SY095 T (=JCM 34213=MCCC 1K04191). An emended description of the genus Crassaminicella is also proposed.